Clinical characteristics and surgical outcomes of paranasal sinus mucoceles at a tertiary referral hospital in Southern Vietnam - Bich Tran, Anh; Chi Le Nguyen, Uyen; Nam Pham, Hoang; Anh Hoang, Van; Huy Truong, Gia; Hieu Tran, Duy; Ton Nu Cam Tu Nguyen, Cong Huyen (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Paranasal sinus mucoceles are increasingly encountered in clinical practice, often presenting with vague and late-stage symptoms. If left untreated, mucoceles can erode adjacent bony structures and compress critical anatomical areas such as the orbit and skull base, leading to serious complications including visual impairment and intracranial involvement. This study aims to describe the clinical and radiological characteristics, microbiological findings, and surgical treatment approaches for paranasal sinus mucoceles.Methods: A descriptive, retrospective study was conducted on 93 adult patients diagnosed and surgically treated for paranasal sinus mucoceles at Cho Ray Hospital, Vietnam, between January 2018 and July 2023. Clinical data, imaging findings, bacterial culture results, and surgical methods were analyzed.Results: The mean patient age was 48 years (range: 18–90), with a male-to-female ratio of 1:1.12. The fronto-ethmoidal region was the most frequently affected site (32.3%). A previous history of nasal/sinus surgery was noted in 50.5% of cases. Common symptoms included proptosis (32.3%), blurred vision (25.7%), facial pain (60.2%), and nasal obstruction (33.3%). For maxillary sinus mucoceles, 60% underwent combined endoscopic and Caldwell-Luc procedures. Among fronto-ethmoidal cases, 72.0% were managed with endoscopic surgery alone, while 25.8% required a combined external Jacques approach. The recurrence rate was 15.1%, with an average time to recurrence of 2.52 years.Conclusions: Paranasal sinus mucoceles often present with nonspecific and ocular-related symptoms. Endoscopic surgery remains the mainstay of treatment, though combined approaches are warranted in complex or recurrent cases. Long-term follow-up is essential to detect recurrences early.